Are Business Regulations Improving Economic Growth? Case Study between ASEAN and European Union - Karuniana Dianta Arfiando Sebayang; Belinda Febrina (Faculty of Economics, State University of Jakarta., 2021)
Economic activities require a transparent regulatory and policy environment that is accessible to all levels of society. This study aims to explain the impact of ease of doing business on economic growth in both ASEAN and the European Union since doing business indicators applied globally. Gross Domestic Product is used as a proxy variable for economic growth as Gross Domestic Product is an indicator to measure economic growth. This study uses a descriptive quantitative research model and uses multiple regressions to determine the effect of ease of doing business on economic growth in ASEAN and the European Union by comparing the result of each ASEAN and European Union. In this study it was found that in ASEAN, there are four indicators of doing business have significant impact to economic growth, while in the European Union five indicators have significant impact to economic growth.